Realizing an online conference: organization, management, tools, communication, and co-creation - Busse, Beatrix; Kleiber, Ingo (International journal of corpus linguistics, 2020)
This paper aims to assist future organizers of international online conferences with designing and realizing these events. On the basis of the authors' experience of having to move a corpus linguistics conference - originally planned as a physical event - into the digital space, this paper describes the conference's organization and management structure, outlines the software and communication tools used and sketches what is important to foster interaction and discourse among participants. The paper contains a manual and a checklist for preparing an online conference, and a discussion of the chances of online and hybrid conferences in terms of outreach, Open Access and co-creation. It ends with an appeal to colleagues to devise conferences with courage, develop new ways of transferring linguistic research findings (to the public) and to move out of their comfort zones to sustainably use the digital transformation for innovative paths of exchanging research findings.
Gesehen am 03.12.2020